251 Molecular Etiology of Childhood Hearing Impairment Associated with Non-Syndromic Enlarged Vestibular Aqueduct in Southeastern China. (October 2012) - Yang, T; Chai, Y; Wu, H
Abstract : Background: Mutations in SLC26A4, and in rarer cases double heterozygous mutations of FOXI1/SLC26A4 or KCNJ10/SLC26A4, lead to childhood hearing impairment associated with non-syndromic enlarged vestibular aqueduct (EVA), the most common inner ear malformation. Molecular etiology studies of non-syndromic EVA will provide important data to facilitate DNA diagnosis and genetic counseling of this disease. Methods: Mutation screening of SLC26A4 was performed in 126 probands with non-syndromic EVA in Southeastern China. Those detected with mono-allelic or no SLC26A4 mutation were subjected to mutation screening of FOXI1 and KCNJ10 . Results: Bi-allelic, mono-allelic, and no SLC26A4 mutation were detected in 70.6%, 8.0% and 21.4% of the probands with non-syndromic EVA. Sixteen of the 40 SLC26A4 mutations detected were novel. While the c.919–2A>G mutation accounted for 41.3% of the mutant alleles of SLC26A4, none of the other 39 mutations accounting for more than 5.6%. No pathogenic FOXI1 or KCNJ10 mutation was identified in this study. Conclusions: The c.919–2A>G mutation of SLC26A4 is highly prevalent and should be the primary target of genetic testing for patients with non-syndromic EVA in Southeastern China. The spectrum of the other SLC26A4 mutations, however, is highly heterogeneous and differs from those reported in Taiwan or other regions of mainland China. Mutations in FOXI or KCNJ10 were not the major cause of non-syndromic EVA in Southeastern China.